Analysis of the Effect of Inorganic Compound Nano Ferric Oxide (Fe2O3) on Increasing Cement Strength - Novrianti, Novrianti; Deswanto, Jefri; Khalid, Idham; Pandjaitan, M. M Lanny W.; Lukas (Journal of Earth Energy Science, Engineering, and Technology, 2024)
The objectives of this research are to analyze the inorganic compound nano-Fe2O3 ironstone for enhancing the compressive and shear bond strength of drilling cement. According to the American Petroleum Association (API), the minimum recommended compressive strength value to continue drilling operations is 500 psi, while the minimum shear bond strength is 100 psi. Nano-Fe2O3 in this study was obtained by synthesizing ironstone from Jorong, West Sumatra, using the coprecipitation method. Based on XRF and XRD tests, 62.8% Fe was obtained in the ironstone compound, and nano-Fe2O3 with the alpha phase was detected using Match 3. Five samples with different concentrations were prepared before starting the cement strength test. The test was conducted following the bio-axial loading test procedure, where each sample will be loaded with a certain amount of load force until the sample breaks. The pressure at the point where the sample broke was recorded as the maximum loading value to determine the compressive strength (CS) and shear bond strength (SBS). The highest CS value obtained was 2536.2953 psi with the addition of 1% nano-Fe2O3, and the highest SBS value obtained was 351.8479 psi with the addition of 1% nano-Fe2O3.